2021
DOI: 10.1101/2021.04.10.21254672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhaled budesonide for COVID-19 in people at higher risk of adverse outcomes in the community: interim analyses from the PRINCIPLE trial

Abstract: BACKGROUND Inhaled budesonide has shown efficacy for treating COVID-19 in the community but has not yet been tested in effectiveness trials. METHODS We performed a multicenter, open-label, multi-arm, adaptive platform randomized controlled trial involving people aged ≥65 years, or ≥50 years with comorbidities, and unwell ≤14 days with suspected COVID-19 in the community (PRINCIPLE). Participants were randomized to usual care, usual care plus inhaled budesonide (800μg twice daily for 14 days), or usual care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
15
0
2
Order By: Relevance
“…This fits with the interim results of a still-ongoing larger phase III trial of 2617 patients, also testing inhaled budesonide therapy for acute SARS-CoV-2 infection [17]. This showed a 3-day shorter time to self-reported clinical improvement of symptoms, but the small effect on COVID-19-related hospitalizations or deaths (budesonide: 59/692 [8.5%] vs. 100/968 [10.3%] patients) was not statistically significant.…”
Section: Evaluation Of the Study Datasupporting
confidence: 81%
See 1 more Smart Citation
“…This fits with the interim results of a still-ongoing larger phase III trial of 2617 patients, also testing inhaled budesonide therapy for acute SARS-CoV-2 infection [17]. This showed a 3-day shorter time to self-reported clinical improvement of symptoms, but the small effect on COVID-19-related hospitalizations or deaths (budesonide: 59/692 [8.5%] vs. 100/968 [10.3%] patients) was not statistically significant.…”
Section: Evaluation Of the Study Datasupporting
confidence: 81%
“…A cautious interpretation of these data is all the more warranted given that an updated interim analysis of data from a larger phase III trial that included 2617 participants with risk factors for unfavorable outcomes with COVID-19 did not show such favorable results [17]-inhaled budesonide shortened time to selfreported recovery by a median of 3 days, but did not meet the primary outcome parameter (predefined superiority threshold for the probability that COVID-19 hospitalizations/deaths were lower in the budesonide group compared with standard therapy): budesonide: 59/692 (8.5%) vs. standard therapy: 100/968 (10.3%) [17].…”
Section: Discussionmentioning
confidence: 99%
“…The PRINCIPLE trial has provided a robust in-pandemic trials platform 2,3,13 The strength of this analysis is that the RSC has good data quality and is able to capture routine data about RTIs and their incidence. 14,15 Comparing the use of azithromycin and doxycycline between years, and their use in RTIs is complex and we are reporting relative change in antibiotic use, their absolute level of use in RTIs is very low.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The Principle trial has shown some promising signs regarding the inhaled drug budesonide, which is usually used to treat asthma and COPD. Interim data from a preprint study, which is yet to be peer reviewed, suggested that the use of budesonide at home for two weeks shortened average recovery times by a median of three days 9…”
Section: What Treatments Work?mentioning
confidence: 99%